1999
DOI: 10.2337/diabetes.48.8.1562
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the hexosamine pathway by glucosamine in vivo induces insulin resistance of early postreceptor insulin signaling events in skeletal muscle.

Abstract: To explore potential cellular mechanisms by which activation of the hexosamine pathway induces insulin resistance, we have evaluated insulin signaling in conscious fasted rats infused for 2-6 h with saline, insulin (18 mU x kg(-1) x min(-1)), or insulin and glucosamine (30 micromol x kg(-1) x min(-1)) under euglycemic conditions. Glucosamine infusion increased muscle UDP-N-acetylglucosamine concentrations 3.9- and 4.3-fold over saline- or insulin-infused animals, respectively (P < 0.001). Glucosamine induced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
154
1
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 228 publications
(175 citation statements)
references
References 0 publications
12
154
1
3
Order By: Relevance
“…This may reflect an involvement by liver, a species difference in the handling of glucosamine, since similar plasma levels of GlcN did induce insulin resistance in the rat [31]. Or it may simply be the result of not achieving sufficiently high levels of intracellular metabolites of the glucosamine pathway in muscle cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This may reflect an involvement by liver, a species difference in the handling of glucosamine, since similar plasma levels of GlcN did induce insulin resistance in the rat [31]. Or it may simply be the result of not achieving sufficiently high levels of intracellular metabolites of the glucosamine pathway in muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…While there is some evidence for the former, there are some discrepancies in the findings. One research group [31] reported that insulinstimulated IRS-1 tyrosine phosphorylation was reduced by glucosamine, whereas another [32] found this was preserved in glucosamine-treated rats. When measured 1 min after a bolus injection of insulin, PI3 kinase (PI3K) activity associated with IRS-1 was decreased by glucosamine infusion, on the other hand, when the activity was measured following 2 h of insulin infusion, no effect of glucosamine was observed [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…UDP-N-acetyl-glucosamine (UDP-Gl c NA c ) and UDP-N-acetyl-galactosamine (UDP-GalNA c ), are highly correlated with the degree of insulin resistance [15]. Others have also shown that incubation of multiple insulin-sensitive rat and human tissues with glucosamine to generate increased concentrations of UDP-Gl c NA c induces insulin resistance [16,17,18,19,20]. Streptozotocin-induced diabetes and sustained hyperglycaemia in normal rats also increase total UDP-hexosamine content in muscle tissue [21].…”
mentioning
confidence: 99%